Application of Training Skills in Nepali Classrooms - Adhikari, Narayan Prasad (ILAM इलम, 2023)
This study aims to explore the application of training skills in Nepali classrooms. The study is conducted through secondary resources, such as websites, document analysis, and evaluating interrelated publications, articles, and journals, to examine one's own insight and sensory experience. Many problems and issues arise when transferring teacher training into classroom practice, including the lack of teachers, inefficient strategies and approaches to training, obsolete curricula, poor supervision services, insufficient empirical research, profit-driven education, etc. Applying teacher training skills in the classroom in Nepal appears to be especially unsuccessful, according to studies with a fifty percent success rate. However, a survey of the literature on teacher training in Nepal that is currently available reveals that not much has been accomplished in this area during the past few decades. This study focuses on theoretical applications, the current situation of teacher preparation, and integrating that knowledge, skill, and attitude into classroom activities.